Nursing process in action - Gardner, Pearl (Australia ; Clifton park, NY : Thomson, Delmar Learning, 2002)
This clear, simple presentation of the nursing process uses many case applications, examples, and lists to help readers develop critical thinking and problem solving skills, with spiritual, cultural, and ethical aspects of care woven throughout. After an overview of the nursing process, chapters cover assessment, diagnosis, planning, implementation, and evaluation. Review questions and answers are included. Gardner teaches in the School of Nursing at the University of Texas-El Paso. Annotation copyrighted by Book News, Inc., Portland, OR.
The nursing process: a synopsis -- Assessment -- Diagnosis -- Planning -- Implementation -- Evaluation.
Includes bibliographical references and index.
Keywords: NURSING